Preclinical study testing feasibility and technical requirements for successful telerobotic long distance peripheral vascular intervention. Issue 3 (18th March 2021) - Legeza, Peter; Sconzert, Kalyna; Sungur, John‐Michael; Loh, Thomas M.; Britz, Gavin; Lumsden, Alan
Abstract: Background: Robotic‐assisted endovascular surgery enables us to perform interventions from long distances. This study evaluates the workflow and telecommunication requirements of telerobotic peripheral vascular interventions. Methods: Ten superficial femoral artery cases were performed by the operator being 44 miles away from the interventional suite, with an endovascular robotic system, on a high‐fidelity endovascular simulator. Procedural success, technical success, fluoroscopy time, residual stenosis, contrast dose and network delay were registered. Communication success was assessed after each procedure on a scale from 1 (unacceptable) to 5 (ideal). Results: Procedural success and technical success were 100% and 80%, respectively. The mean residual stenosis, fluoroscopy time and contrast dose were 1.7 ± 5.25%, 6.5 ± 1.8 min and 58.8 ± 14.8 ml. The mean network latency was 38.9 ± 3.5 ms. Median communication success scores were 4.5 (min: 4, max: 5) reported by both the operator and the bedside technician on a scale of 1 (unacceptable) to 5 (ideal). Conclusion: With a stable network connection and good communication protocol, a high success rate was achieved for remote robotic‐assisted peripheral vascular intervention in an ex vivo model.